2016
DOI: 10.1007/s11060-016-2280-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating patients for psychosocial distress and supportive care needs based on health-related quality of life in primary brain tumors: a prospective multicenter analysis of patients with gliomas in an outpatient setting

Abstract: The association between health-related quality of life (HRQoL), psychosocial distress, and supportive care is in the focus of patient-centered neuro-oncology. We investigated the relationship between the aforementioned in glioma-patients to evaluate the association of these instruments and determine cut-off values for suitable HRQoL scales indicating a potential need for intervention. In an observational multi-center study, outpatients completed the Distress Thermometer (DT), EORTC Quality of Life Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
3
27
0
3
Order By: Relevance
“…Other studies have attempted to define thresholds for the QLQ-C30 using ad hoc criteria. Hickmann et al [11] developed thresholds for six functioning and symptom domains using distress and supportive care needs separately as criteria. For the latter criterion, Hickmann et al reported the same thresholds for RF, CF, and SF as in our study, whereas thresholds for PF and FA were higher.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have attempted to define thresholds for the QLQ-C30 using ad hoc criteria. Hickmann et al [11] developed thresholds for six functioning and symptom domains using distress and supportive care needs separately as criteria. For the latter criterion, Hickmann et al reported the same thresholds for RF, CF, and SF as in our study, whereas thresholds for PF and FA were higher.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we concentrated on striking results regarding superordinate aspects of the questionnaire like global health, future uncertainty and QOL based on the following considerations: (1) to keep the evaluation as simply and suitable for daily use as possible (1) because of our inclusion criteria next to brain tumors our patients comprised different neurosurgical diagnoses, therefore we neglected brain tumor specific aspects (2) at the time of assessment our patients presented a median KPS of 90 without major neurologic deficits, thus we did not pay attention toward special functional and symptom scales. Additionally, a recent analysis highlighted future uncertainty and global health status especially in brain tumor patients as very important and correlated with unmet needs in these patients [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a larger multicenter study Hickmann et al presented data of 167 neurooncological outpatients analyzing results of the distress thermometer, the EORTC QLQ-C30/BN 20 as well as the Supportive- Care-Needs- Survey- SF34-G (SCNS). They observed a strong correlation of elevated distress and fatigue, cognitive- emotional function, global health status and future uncertainty [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted several observational studies before that led to the research question of the GLIOPT trial. Hereby we found that 1) some questionnaires do not fit to the requirements of HGG patients (6,11), 2) patients in reduced clinical condition with high unmet needs may be missed by a questionnaire or tablet assessment (8,12) and 3) we can use "signaling items" probably indicating patients in need of support (13). Applying these items in a face-to-face conversation of doctor and patient was possible.…”
Section: Preliminary Workmentioning
confidence: 95%